Sistem Monitoring Lahan Parkir Kendaraan pada Yayasan Teratai Putih Global menggunakan Sensor Ultrasonik dan MQTT berbasis Aplikasi Mobile - Andhika Rizky Fariz; Mochammad Hannats Hanafi Ichsan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The Teratai Putih Global Foundation, an Islamic education foundation in Indonesia, has been facing parking problems due to the spread-out and far apart parking lots. To address this issue, a study was conducted to design a parking monitoring system based on a mobile application. The system uses ESP32, Ultrasonic Sensors, and MQTT Brokers and is divided into two systems for each type of parking. For motorbike parking, a counter system is used to count the number of motorbikes entering and exiting the parking lot. For car parking, a timer system displays an occupied parking indicator once a car parks in a slot. The two systems are linked by MQTT and displayed via a mobile application, allowing users to monitor parking availability remotely and in real time. This parking monitoring system can help the Global White Lotus Foundation and other organizations or businesses facing similar parking problems. The use of IoT technology in parking management is a promising solution that can significantly improve the parking experience for both users and providers. By allowing remote monitoring of parking availability, this system helps to overcome the challenges faced by the community, making it easier to find available parking spaces.